Nature of the acid sites in the metal triflates immobilized in SBA-15 and their role in the friedel-crafts acylation of naphthalene - Selvakumar, S.; Gupta, Narendra M.; Singh, A. P. (Applied Catalysis A-General, 2010)
The Zn-triflate molecules loaded (5-30 mol%) in mesoporous SBA-15 silicate exhibited considerably higher catalytic activity for liquid-phase Friedel-Crafts (FC) acylation of naphthalene with p-toluoyl chloride, as compared to the corresponding triflates of La, Ce and Y. In situ FTIR studies revealed that the triflate molecules occluded in the channels of SBA-15 may cause severe perturbation of surface hydroxyl groups, without undergoing an electronic binding. The metal cations of the triflate molecules, on the other hand, participated in direct bonding of the reactant molecules and also helped in the formation of some Bronsted type surface acid sites. This article discusses the role of the acid sites generated on occlusion of metal triflates in SBA-15, as monitored by using NH(3)-TPD and pyridine-IR spectroscopy, in the Friedel-Crafts acylation of naphthalene. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acylation; Mesoporous silica; Metal triflate; Naphthalene

Novel, band-controlled metal oxide compositions for semiconductor-mediated photocatalytic splitting of water to produce H-2 - Gupta, Narendra M. (57th DAE Solid State Physics Symposium, 2013)
57th DAE Solid State Physics Symposium, Indian Inst Technol, Bombay, INDIA, DEC 03-07, 2012